KERJASAMA RUSIA-TIONGKOK DALAM SEKTOR ENERGI: SUATU TINJAUAN HERMENEUTIK - Dhiva Pratiwi, Aprillia Ayunda; Wonoadi, Grace Lestariana (CONVERGENCE: JOURNAL OF GLOBAL DYNAMICS, 2025)
Energy security is a key issue in international relations. As the world's leading supplier of natural gas, Russia's 2014 initiative to secure energy sector cooperation with China is significant. This study aims to identify the interests behind this collaboration. As a case study, this research applies a hermeneutic approach that provides space for interpretive explanatory analysis. This research integrates document analysis related to the historical, geopolitical, and strategic context surrounding the cooperation. Secondary data from credible sources, both printed and digital ones, are the main references. The results indicate that this cooperation is driven by several key factors. First, Russia has abundant natural gas resources and has the potential to increase state revenue. It needs a committed, large, and stable market. Second, China has an ever-increasing need for energy due to its rapid industrialization. Russian natural gas could meet some of China's energy needs and reduce its dependence on other imported energy supplies. Third, this cooperation also has important political and security dimensions for regional stability and strengthening their position in global geopolitics post Euromaidan Revolution.